Challenges of dissemination of Islam-related information for Chinese Muslims in China - Ma, Ting; Ramli, Romlah; Abdul Rahman, Nik Adzrieman (Universitas Semarang, 2018)
This article provided a historical background of the challenges faced in the course of Islamic education of Chinese Muslims in the context of social change. The researcher historically evaluated how social change reshaped the Islamic education of Chinese Muslims, and highlighted the influence of technical development on Islamic education in contemporary China. The available research indicated that since the 1980s, the challenges faced in the course of Islamic education of Chinese Muslims have gradually shifted from political repercussions to technological development. Due to the limited literature, the researcher called for more research on new media development, especially social media and Muslim minority groups in China. The researcher also proposed a research agenda for future studies.